STRATEGI GURU DALAM MEMBENTUK KARAKTER SISWA MI TERPADU MUTIARA KOTA PADANGSIDIMPUAN - Sormin, Darliana; Rahma Rangkuti, Fatimah (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2018)
This research is about teacher’s strategues in forming the students’ characters at Madrasah Ibtidaiyah Terpadu Mutiara Padangsidimpuan. There is a special character of this school in implementing characterized curriculum based fitrah. It ws done qualitatively by describing the phenomeneon in the field. The teachers’ strategies are gpd, and the students can apply the characters in their daily life, in school and at home as an Islamic teaching. The teachers’ strategies in forming the students’ characters through applying the active partisipatory learning, creating the condusive learning environment, giving eduacted character explisitly, sistematically, and continuosly by involving moral knowing, moral feeling, and moral action aspects